Carvedilol activates nuclear factor E2-related factor 2/ antioxidant response element pathway to inhibit oxidative stress and apoptosis of retinal pigment epithelial cells induced by high glucose. Issue 1 (1st January 2022) - Zhang, Yu; Li, Mingcun; Wang, Weixing; He, Siyu
ABSTRACT: Diabetic retinopathy (DR) is the most prominent manifestation of diabetic microangiopathy and is a serious complication of diabetes. Despite extensive researches focusing on DR, treatment options for DR are still limited. Carvedilol (CAR) has vasodilatory, antioxidant stress and anti-inflammatory effects and poses a vital role in addressing the issue of diabetic complications. This paper attempts to explore this property of CAR and investigate into its effects on DR. First, ARPE-19 cells were treated with different concentrations of CAR and cells were induced with 30 mM high glucose (HG) to establish a DR cell model. Cell viability was assayed by cell counting kit-8 (CCK-8) with or without HG induction. Cellular inflammation and oxidative stress were evaluated by enzyme-linked immunosorbent assay (ELISA) and corresponding kits. The measurement of apoptosis levels was conducted by Terminal dUTP nick-end labeling (TUNEL) and Western blotting. The protein levels related to Nrf2/ARE signaling pathway were assessed by Western blotting. Finally, cellular inflammation, oxidative stress and apoptosis in ARPE-19 cells pretreated with Nrf2 inhibitor ML385 were tested again by the same methods. Results showed that under HG induction, CAR effectively improved ARPE-19 cell viability, inhibited cellular inflammation, oxidative stress, and apoptosis. Moreover, CAR activated Nrf2/ARE signaling pathway, which further suppressed cellular inflammation, oxidative stress, and apoptosis. Overall, CAR inhibited HG-induced oxidative stress and apoptosis in retinal pigment epithelial cells by activating Nrf2/ARE pathway.